Curadoria em rede de conhecimento agroecológico e desenvolvimento territorial: protocolo para integração e difusão de materiais técnico-científicos congêneres - Alves, Renato Marques (2025)
In the era of networked services, one of the topics that has been the subject of studies at Universities and Research Institutions is the development of tools for sharing data from publications and other digital materials between institutions. Among the numerous reasons for these studies, collaborative information governance stands out as one of the key interfaces for network integration, along with the expansion of interoperable information systems and the essential role of curation in permanent digital preservation. However, one of the challenges faced is finding ways to materialize a service for sharing data and technical-scientific texts from peer organizations, because on the one hand, there is the decentralized process of production, management and distribution of knowledge; and on the other, the difficult task of controlling partner institutions to keep the data on productions generated updated, through voluntary collaboration. Given the scenario outlined above, a study was developed using the Postgraduate Program in Agroecology and Territorial Development (PPGADT) as an empirical reference in association with 03 Public Universities, whose flows of collection, storage, processing and sharing of technical-scientific productions are the responsibility of each associated university. In the preliminary assessment, information problems were identified, specifically in relation to the dispersion and fragmented management of information. The implications vary, such as potential risks of duplication of work in the research lines; difficulties in quickly accessing data on publications and even in their recovery. Based on this, the question was: how to develop a protocol based on the concept of a network for the integration and dissemination of knowledge produced in the PPGADT network. The general objective was to develop a protocol for the integration and dissemination of knowledge in the network that forms the Postgraduate Program in Agroecology and Territorial Development (PPGADT), based on institutional repositories. The research method used was the Multiple Case Study (three selected cases), through a combination of research techniques for collecting and producing research data. The results showed that PPGADT members adopt practices for organizing publications on various research platforms/directories, as well as on academic social networks. Regarding searches for internal publications, they report that they find it easy to retrieve theses and final products, but have difficulty locating other materials produced during their training. Library professionals report a shortage of human resources for both curation activities and ongoing technical maintenance of digital repositories, as structural problems that impact the collection and management of all local academic production. The study concludes by presenting some alternatives for removing the barriers that limit access to publications and lists recommendations for an information sharing service on agroecology and territorial development among peer institutions.scientific information between PPGADT centers